Description of Spiritual Development for the Erderly at Panti Sosial Tresna Werdha (PSTW) Sabai Nan Aluih, Padang Pariaman - Nugraheni, Verly (Universitas Negeri Padang, 2019)
The research is motivated by the activity of the elderly in participating in spiritual activities carried out by social institutions tresna werdha Sabai Nan Aluih Sicincin district Padang Pariaman. This study aims to describe the implementation of spiritual guidance on development activities: (a) aqidah, (b) worship and (c) morals. The population was all elderly healthy and able to follow the activities of spiritual formation as much as 98 elderly. Sampling in this study using cluster random sampling as many as 24 elderly. The data collection technique using closed interviews. Data analysis techniques using a percentage formula. The research result shows that (a) picture of moral development activities carried out by social institutions tresna excellent Werdha (b) picture of worship development activities carried out by social institutions tresna excellent Werdha, and (c) picture of moral development activities carried out by social institutions tresna Werdha very good.Keywords: Aqidah, Worship, Morals